PENGEMBANGAN BAK PENDARATAN LOMPAT JAUH DALAM PEMBELAJARAN PENJASORKES - Probo Winasis; Rumini (Universitas Negeri Semarang, 2016)
The purpose of this study is to produce learning tools penjasorkes middle school students through the development of long jump landing tub. This research is a development. The data collection was conducted using questionnaires obtained from the evaluation experts and kueioner students and use the results of field observations. Technical analysis of the data used is descriptive percentage. The average yield on the expert validation trials small group obtained a percentage of 85%, the average yield of the student questionnaire on small group trial was obtained by 82.37%. Of the average yield of expert validation in a large group trial was obtained by 94%, while the average yield kueioner students in a large group trial was obtained by 93.36%. Based on the research results, it can be concluded that the development of the long jump landing tub is suitable for use in penjasorkes learning for students of SMP N 1 Ajibarang.